Symmetrical and Asymmetrical Fault Currents: Evaluation to Enhance the Performance of 220KV Grid Station - Tahir, M. J.; Latiff, I. A.; Gul, M. U.; Alam, M.; Mazliham, M. S. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The studies of the electrical system need to assess the output of the power system at development phase as well as daily situations. This paper presents fault current study of a 220KV grid station at the standard of IEC 60909 and IEC 61363. In order to support the power system, fault current study can be done at design & development phase to conclude the system design, determine voltage magnitude, shielding apparatus, circuit breakers, conductor length, step up and step-down power equipment and solid grounding. A grid station is simulated using real system facts and Figures in the ETAP software and fault current analysis is executed at different voltage levels. With the help of results achieved from the simulations, it is likely to assess the dynamic pressure yield to the equipment of the power system in the existence of faults. However, evaluation of installed apparatus in the situation of power system enhancement that can significantly influence the fault current level. The study shows the significance of the symmetrical and asymmetrical fault currents investigation for the description of the apparatus rating, which must upkeep these currents.